2011
DOI: 10.5897/ajbm11.1191
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the intention to use Facebook to support problem-based learning among employees in a Taiwanese manufacturing company

Abstract: This study offers an approach for understanding factors influencing employees' acceptance and usage of Facebook as an assisted learning tool in Problem-based Learning (PBL). Based on the Technology Acceptance Model (TAM), the objectives of this study are to explore behavioral intention and the factors (perceived usefulness (PU), perceived ease of use (PEU), social influence (SI), perceived enjoyment (PE), concentration (C) and computer self-efficacy (CSE) affecting Facebook use for assisted PBL. A survey was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Previous research also showed that perceived enjoyment increased students' intention to use e-learning (e.g. Cheng, 2012;Yang & Lin, 2011;Zare & Yazdanparast, 2013).…”
Section: Perceived Enjoymentmentioning
confidence: 83%
“…Previous research also showed that perceived enjoyment increased students' intention to use e-learning (e.g. Cheng, 2012;Yang & Lin, 2011;Zare & Yazdanparast, 2013).…”
Section: Perceived Enjoymentmentioning
confidence: 83%
“…A user's own perceived abilities have been shown to affect attitudes towards technology in terms of selfefficacy (Abbad et al, 2009;Al-Gahtani, 2014;Chen et al, 2007;Cheng, 2011;Lee, 2006;Motaghian et al, 2013;Shen & Eder, 2009;Yang & Lin, 2011), internet experience (Abbad et al, 2009), andcomputer anxiety (Al-Gahtani, 2014). Whereas self-efficacy is "a person's judgement of what one can do with whatever skills one possesses" (Bandura, 1986, p. 391), and internet experience is an objective measure related to one's usage history, user anxieties are related to the affective axis and more about how the user feels.…”
Section: Perceived Anxiety (Pa)mentioning
confidence: 99%
“…Using Webster and Martocchio's framework, various researchers used playfulness as an intrinsic motivation construct added to the basic TAM model in their studies (Atkinson & Kydd, 1997;Moon & Kim, 2001;Venkatesh, 2000). These two elements of intrinsic motivation are found to affect adoption and continued use of new technologies (Teo, Lim, and Lai 1999;Koufaris 2002;Oum and Han 2011;Heijden 2004;Agrifoglio and Black 2012;Yang and Lin 2011;Davis, Bagozzi, and Warshaw 1992;Atkinson and Kydd 1997;Moon and Kim 2001;Thong, Hong, and Tam 2006;Barnes 2011;Leng and Lada 2011;Lee, Xiong, and Hu 2012;Hsu and Lin 2008). In line with previous studies "enjoyment" and "playfulness" are used as constructs for measuring intrinsic motivation of individuals in this study.…”
Section: Underlying Theoriesmentioning
confidence: 99%